2021
DOI: 10.4149/bll_2021_086
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of a vaccine against COVID-19 – a systematic review of surveys conducted worldwide

Abstract: OBJECTIVES: The most promising strategy for managing COVID-19 pandemic is achieving suffi cient vaccination rate worldwide. The question is how many people will be willing to get vaccinated. STUDY DESIGN: We systematically reviewed peer-reviewed manuscripts monitoring people´s intention to receive a vaccine against COVID-19. METHODS: Up to December 28, 2020 we identifi ed 62 relevant peer-reviewed articles in PubMed, Web of Science, Scopus and GoogleScholar. RESULTS: Total sample size was 118 855 respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…The wide range of parents' willingness among studies is confirmed by similar reviews in the general population and could be due to different study designs, study populations, levels of knowledge and information, attitudes towards vaccination etc. (Galanis et al, 2021;Snehota et al, 2021;. Interestingly, we did not find differences in parents' willingness to vaccinate their children according to the continent that studies were conducted.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…The wide range of parents' willingness among studies is confirmed by similar reviews in the general population and could be due to different study designs, study populations, levels of knowledge and information, attitudes towards vaccination etc. (Galanis et al, 2021;Snehota et al, 2021;. Interestingly, we did not find differences in parents' willingness to vaccinate their children according to the continent that studies were conducted.…”
Section: Discussioncontrasting
confidence: 44%
“…We found that the overall proportion of parents that intend to vaccinate their children against the COVID-19 is moderate (56.8%) with a wide range among studies from 29% to 72.7%. Parents' intention to vaccinate their children against the COVID-19 is lower than intention of the general population to take a COVID-19 vaccine (56.8% vs. 73%) (Snehota et al, 2021;. Also, the willingness of high-risk groups such as healthcare workers to accept COVID-19 vaccination is higher than parents' willingness to vaccinate their children (63.5% vs. 56.8%) (Galanis et al, 2020;Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…COVID-19 vaccine acceptance shows a great variability across countries or regions which may affect the efforts to contain the pandemic (Aw et al, 2021). According to meta-analyses (Snehota et al, 2021; Q Wang et al, 2021), the average COVID-19 vaccine acceptance rate in the general population is about 73% which is lower than the percentage estimated to be sufficient for reaching herd immunity threshold with a COVID-19 vaccine that is at least 80% effective (Bartsch et al, 2020). Moreover, the longer the COVID-19 pandemic lasts, the smaller rate of the general population wants to get vaccinated (Snehota et al, 2021).…”
Section: Introductionmentioning
confidence: 99%